2018
DOI: 10.1007/s10461-018-2184-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving PrEP Implementation Through Multilevel Interventions: A Synthesis of the Literature

Abstract: There are many challenges to accessing PrEP and thus low uptake in the United States. This review (2007–2017) of PrEP implementation identified barriers to PrEP and interventions to match those barriers. The final set of articles (n = 47) included content on cognitive aspects of HIV service providers and individuals at risk for infection, reviews, and case studies. Cognitive barriers and interventions regarding patients and providers included knowledge, attitudes, and beliefs about PrEP. The “purview paradox” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
135
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 72 publications
10
135
0
Order By: Relevance
“…In addition, research regarding low access, uptake, and adherence to PrEP has shown breakdowns in healthcare systems implementing PrEP, a lack of medical providers' knowledge or willingness to prescribe PrEP (Krakower, Ware, Mitty, Maloney, & Mayer, ; Petroll et al., ), and unfavorable community attitudes about PrEP (Krakower et al., ; Liu et al., ). These barriers reflect those we have witnessed for the past 20 years in relation to CDC DEBIs, which have been discussed at length (Dworkin et al., ; Pinto, Berringer, et al., ; Pinto, Witte, et al., ). These barriers to intervention implementation also reflect both the political climate and community exclusion from implementation decision‐making.…”
Section: De‐implementation Of Behavioral Interventions and The Surgesupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, research regarding low access, uptake, and adherence to PrEP has shown breakdowns in healthcare systems implementing PrEP, a lack of medical providers' knowledge or willingness to prescribe PrEP (Krakower, Ware, Mitty, Maloney, & Mayer, ; Petroll et al., ), and unfavorable community attitudes about PrEP (Krakower et al., ; Liu et al., ). These barriers reflect those we have witnessed for the past 20 years in relation to CDC DEBIs, which have been discussed at length (Dworkin et al., ; Pinto, Berringer, et al., ; Pinto, Witte, et al., ). These barriers to intervention implementation also reflect both the political climate and community exclusion from implementation decision‐making.…”
Section: De‐implementation Of Behavioral Interventions and The Surgesupporting
confidence: 62%
“…The fast shift from behavioral to medical interventions has inherent barriers to implementation (Pinto, Berringer, Melendez, & Mmeje, ), and the surge of HIV‐prevention biomedical interventions has exacerbated already existing racial and gender disparities in HIV prevention and treatment—for instance, disproportionately low PrEP uptake among black MSM (Eaton, Driffin, Bauermeister, Smith, & Conway‐Washington, ), who represent a historically underserved population. In addition, research regarding low access, uptake, and adherence to PrEP has shown breakdowns in healthcare systems implementing PrEP, a lack of medical providers' knowledge or willingness to prescribe PrEP (Krakower, Ware, Mitty, Maloney, & Mayer, ; Petroll et al., ), and unfavorable community attitudes about PrEP (Krakower et al., ; Liu et al., ).…”
Section: De‐implementation Of Behavioral Interventions and The Surgementioning
confidence: 99%
“…[25][26][27][28][29][30] Others have studied provider barriers to PrEP implementation, finding that provider education is an important aspect of PrEP access. 22,[31][32][33][34][35] Few studies have examined patient experiences outside of research settings, mainly exploring experiences within specific clinics and programs already designed to deliver PrEP. 22,27,[36][37][38][39] While these findings are helpful for implementation, little is known about PrEP use in less controlled settings where providers may not be equipped to prescribe PrEP and potential PrEP users may not receive the same level of support.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple comprehensive literature reviews have been published describing these barriers and facilitators at the patient, provider, and systems levels. [1][2][3][4] In 2018, Pinto et al 5 published a particularly useful synthesis of barriers to PrEP implementation across levels, with corresponding strategies designed to address these barriers.…”
Section: Introductionmentioning
confidence: 99%